Seismic behaviour of traditional timber frame walls: experimental results on unreinforced walls - Poletti, Elisa (2015)
Timber frame buildings are well known as an efficient seismic resistant structure and they are used worldwide. Moreover, they have been specifically adopted in codes and regulations during the XVIII and XIX centuries in the Mediterranean area. These structures generally consist of exterior masonry walls with timber elements embedded which tie the walls together and internal walls which have a timber frame with masonry infill and act as shearwalls. In order to preserve these structureswhich characterizemany cities in theworld it is important to better understand their behaviour under seismic actions. Furthermore, historic technologies could be used even in modern constructions to build seismic resistant buildings using more natural materials with lesser costs. Generally, different types of infill could be applied to timber frame walls depending on the country, among which brick masonry, rubble masonry, hay and mud. The focus of this paper is to study the seismic behaviour of the walls considering different types of infill, specifically: masonry infill, lath and plaster and timber frame with no infill. Static cyclic tests have been performed on unreinforced timber frame walls in order to study their seismic capacity in terms of strength, stiffness, ductility and energy dissipation. The tests showed how in the unreinforced condition, the infill is able to guarantee a greater stiffness, ductility and ultimate capacity of the wall.